Letting the 'cat' out of the bag: pouch young development of the extinct Tasmanian tiger revealed by X-ray computed tomography. Issue 2 (21st February 2018) - Newton, Axel H.; Spoutil, Frantisek; Prochazka, Jan; Black, Jay R.; Medlock, Kathryn; Paddle, Robert N.; Knitlova, Marketa; Hipsley, Christy A.; Pask, Andrew J.
Abstract : The Tasmanian tiger or thylacine ( Thylacinus cynocephalus ) was an iconic Australian marsupial predator that was hunted to extinction in the early 1900s. Despite sharing striking similarities with canids, they failed to evolve many of the specialized anatomical features that characterize carnivorous placental mammals. These evolutionary limitations are thought to arise from functional constraints associated with the marsupial mode of reproduction, in which otherwise highly altricial young use their well-developed forelimbs to climb to the pouch and mouth to suckle. Here we present the first three-dimensional digital developmental series of the thylacine throughout its pouch life using X-ray computed tomography on all known ethanol-preserved specimens. Based on detailed skeletal measurements, we refine the species growth curve to improve age estimates for the individuals. Comparison of allometric growth trends in the appendicular skeleton (fore- and hindlimbs) with that of other placental and marsupial mammals revealed that despite their unique adult morphologies, thylacines retained a generalized early marsupial ontogeny. Our approach also revealed mislabelled specimens that possessed large epipubic bones (vestigial in thylacine) and differing vertebral numbers. All of our generated CT models are publicly available, preserving their developmental morphology and providing a novel digital resource for future studies of this unique marsupial.